Advanced water quality studies using sensorial methods and indicators - Pandan, Mary Ann T. (College of Engineering, University of the Philippines Diliman, 2015)
Most water management methodologies require comprehensive studies and thus, entail voluminous data, time and scientific expertise. Strategies involving sensorial evaluation such as (a) visual and (b) odor assessment which involve public participation were thus, considered. This study applied visual and odor methodologies to Sarno River, Italy and aimed to validate its reliability as a tool for river assessment. The relationships between sensorial and traditional analytical parameters were also explored. The visual assessment scores and odor measurements proved to be correlated to organic content of the river, indicating that it can be an alternative indicator of water quality in rivers. The approach was also used in testing its applicability to a similarly polluted river system in the Philippines. Visual, biological and analytical methods were applied in the case of Marikina River and it was found that the integration of these methods is very useful in getting more information on the ecological condition of the river. The novel procedures used in visual assessment, odor assessment and bioassays may also be utilized in further studies.